English-based Pediatric Emergency Medicine Software Improves Physician Test Performance on Common Pediatric Emergencies: A Multicenter Study in Vietnam - Lin, Michelle (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2013)
INTRODUCTION: Global health agencies and the Vietnam Ministry of Health have identified pediatric emergency care and health information technology as high priority goals. Clinical decision support (CDS) software provides physicians with access to current literature to answer clinical queries, but there is limited impact data in developing countries. We hypothesized that Vietnamese physicians will demonstrate improved test performance on common pediatric emergencies using CDS technologies despite being in English. METHODS: This multicenter, prospective, pretest-posttest study was conducted in 11 Vietnamese hospitals enrolled a convenience sample of physicians who attended an 80-minute software training on a pediatric CDS software (PEMSoft). Two multiple-choice exams (A, B) were administered before and after the session. Participants, who received Test A as a pretest, received Test B as a posttest, and vice versa. Participants used the CDS software for the posttest. The primary outcome measure was the mean percentage difference in physician scores between the pretest and posttest, as calculated by a paired, two-tailed t-test. RESULTS: For the 203 participants, the mean pretest, posttest, and improvement scores were 37% (95% CI: 35–38%), 70% (95% CI: 68–72%), and 33% (95% CI: 30–36%), respectively, with p<0.0001. This represents an 89% improvement over baseline. Subgroup analysis of practice setting, clinical experience, and comfort level with written English and computers showed that all subgroups equivalently improved their test scores. CONCLUSION: After brief training, Vietnamese physicians can effectively use an English-based CDS software based on improved performance on a written clinical exam. Given this rapid improvement, CDS technologies may serve as a transformative tool in resource-poor environments.